2009
DOI: 10.1016/j.psyneuen.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the cannabinoid regulation of energy homeostasis

Abstract: Summary This review highlights the progress made thus far in characterizing the behavioral and cellular mechanisms through which cannabinoids regulate energy homeostasis. We performed microstructural analysis of feeding behavior in gonadectomized guinea pigs and gonadally intact, transgenic CB1 receptor knockout mice to determine how cannabinoids affect circadian rhythms in food intake and meal pattern. We also implanted data loggers into the abdominal cavity to correlate the appetite-modulating properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
5
24
0
Order By: Relevance
“…We found that cigarette smoking in males modifies the association between cannabis use and change in adiposity. Sex differences at the level of the pro-opiomelanocortin (POMC) neuron synapse, which are involved in stress response, feeding behavior and weight gain, may partly explain the interaction (Farhang et al, 2009). CB 1 activation of these synapses results in increased excitation in females and in inhibition in male animals (Farhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that cigarette smoking in males modifies the association between cannabis use and change in adiposity. Sex differences at the level of the pro-opiomelanocortin (POMC) neuron synapse, which are involved in stress response, feeding behavior and weight gain, may partly explain the interaction (Farhang et al, 2009). CB 1 activation of these synapses results in increased excitation in females and in inhibition in male animals (Farhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences at the level of the pro-opiomelanocortin (POMC) neuron synapse, which are involved in stress response, feeding behavior and weight gain, may partly explain the interaction (Farhang et al, 2009). CB 1 activation of these synapses results in increased excitation in females and in inhibition in male animals (Farhang et al, 2009). POMC synapses are also influenced by nicotine through a nicotine receptor located on its membrane (Mineur et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study also demonstrated that male but not female CNR1 knockout mice had diminished nocturnal food intake and average daily body weight as compared to their wild type littermates. In addition, gonadectomized guinea pigs showed considerably more robust stimulation of intake in males than in females 18) . In this study, while CNR1 4895 C/T polymorphism showed a significant association with WC, no significant association was found with central obesity based on WC.…”
Section: Fundingmentioning
confidence: 95%
“…ORL-1 can act at the presynaptic terminal to inhibit neurotransmitter release to the β-END neuron through reducing the activity of voltage-gated calcium channels (Farhang, Diaz, Tang, & Wagner, 2009). For example, OFQ/N presynaptically inhibits excitatory glutamatergic input to ARH neurons (Emmerson & Miller, 1999;Wagner et al, 1998).…”
Section: Ovarian Steroid Regulation Of Ofq/n and Orl-1 Expression Andmentioning
confidence: 99%